2020
DOI: 10.3390/microorganisms8050761
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Presence of Hepatitis E Virus in Surface Water and Drinking Water in Portugal

Abstract: Hepatitis E virus (HEV) is a non-enveloped single-stranded positive-sense RNA virus, belonging to the Hepeviridae family, resistant to environmental conditions, and transmitted by the consumption of contaminated water. This virus is responsible for both sporadic and epidemic outbreaks, leading to thousands of infections per year in several countries, and is thus considered an emerging disease in Europe and Asia. This study refers to a survey in Portugal during 2019, targeting the detection and eventual quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 60 publications
2
28
0
1
Order By: Relevance
“…In Portugal, NoV and HAV RNAs had not yet been found in drinking water, namely in a recent study [44]. However, another enteric virus (HEV) was detected in the drinking water sampled in this study, as was already referred to above for surface water samples [48]. Concerning other countries, Kukkula et al (1999) [35] detected NoV II RNA in drinking water from various sources in Finland and, more recently, Blanco et al (2017) [36] detected NoV I and NoV II RNA in drinking water in Spain, in concentrations (327.0-660.0 gc/L) higher than in the present study.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…In Portugal, NoV and HAV RNAs had not yet been found in drinking water, namely in a recent study [44]. However, another enteric virus (HEV) was detected in the drinking water sampled in this study, as was already referred to above for surface water samples [48]. Concerning other countries, Kukkula et al (1999) [35] detected NoV II RNA in drinking water from various sources in Finland and, more recently, Blanco et al (2017) [36] detected NoV I and NoV II RNA in drinking water in Spain, in concentrations (327.0-660.0 gc/L) higher than in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…HAV RNA, not detected in the present study in surface waters, was detected in Peri Lagoon in Brazil [58] at relatively high concentrations (1.1 × 10 2 to 4.3 × 10 3 gc/L). In Portugal, Teixeira et al (2020) [44] did not detect viruses in superficial water intended for drinking water production, but Salvador et al (2020) [48] reported, for surface water samples included in this study (from the river and the dam reservoir), the detection of hepatitis E virus (HEV), which is an enteric virus not included in the present study.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations